An outcome evaluation of the Shine Centre's literacy hour programme - Schkolne, Deborah Stacey (Institute for Monitoring and Evaluation, 2015)
This dissertation reports on an outcome evaluation of The Shine Centre's literacy intervention, Literacy Hour. The Shine Centre is a South African non-governmental organisation that offers literacy support to Grade 2 and 3 learners at risk of reading failure. The programme takes the form of one-to-one or one-to-two tutoring. The learners who are chosen to participate in the Literacy Hour programme are selected based on their results in Shine's diagnostic assessment completed at the end of Grade 1. The selected students work with trained volunteers twice a week for an hour at a time. Each hour of the Literacy Hour programme is divided into four 15-minute components, namely: (a) paired reading, (b) shared reading, (c) have-a-go writing, and (d) wordplay. The evaluation design was a quasi-experimental, non-equivalent group design. The assignment into the experimental/intervention group and the control group was done by means of a sharp regression-discontinuity cut-off. The sample included six Centres and two Chapters in the Western Cape with complete data for the 2011 to 2013 cohort. Learner results were monitored using various assessment tools at the end of Grade 1 and during Grades 2 and 3. The two Shine diagnostic assessments, D1 and D2, tested the learners' literacy skills against the level that they should have acquired by that point in their school career. Additionally, the reading level assessments were used to determine the learners' actual reading level/age.